2023
DOI: 10.3389/fpubh.2023.1170584
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-term exposure to ambient particulate matter and pulmonary function among men and women in typical areas of South and North China

Abstract: BackgroundStudies comparing the effects of different sizes and concentrations of ambient particulate matter (PM) on pulmonary function in different regions and sexes remain sparse.ObjectivesTo investigate the associations of different sizes and levels of long-term ambient PM exposure with pulmonary function among people of different sexes in typical areas of South and North China.MethodsIn 2021, a total of 1,592 participants aged 20–73 years were recruited to participate in the pulmonary function test from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…As reported, a densely populated community are likely to emit more air pollutants ( 97 ) that contribute to an increase in risk of obesity ( 98 , 99 ). Moreover, population density has a positive correlation with PM 10 concentration ( 100 ), and elevated PM 10 levels have been shown to compromise lung function ( 101 , 102 ), consequently impacting cardiovascular health ( 103 ). Interestingly, research have indicated that an increase in coverage ratio of greenspaces benefits to lower the prevalence of obesity ( 104 ), hypertension and cardiovascular disease ( 105 , 106 ), as well as reduce the mortality of cardiovascular disease ( 107 , 108 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, a densely populated community are likely to emit more air pollutants ( 97 ) that contribute to an increase in risk of obesity ( 98 , 99 ). Moreover, population density has a positive correlation with PM 10 concentration ( 100 ), and elevated PM 10 levels have been shown to compromise lung function ( 101 , 102 ), consequently impacting cardiovascular health ( 103 ). Interestingly, research have indicated that an increase in coverage ratio of greenspaces benefits to lower the prevalence of obesity ( 104 ), hypertension and cardiovascular disease ( 105 , 106 ), as well as reduce the mortality of cardiovascular disease ( 107 , 108 ).…”
Section: Discussionmentioning
confidence: 99%